Highly selective environmental sensors based on flame-spray-made SnO 2 nanoparticles - Liewhiran C. (2014)
Flame-spray-made SnO 2 thick films fabricated by spin coating method were studied for toxic and flammable gas-sensing applications. From physical characterization by X-ray diffraction, Brunauer-Emmett-Teller analysis, scanning and transmission electron microscopy, SnO 2 nanoparticles were found to have non-agglomerated spherical, hexagonal, rectangle (3-10 nm), and rod-like (3-5 nm in width and 5-20 nm in length) morphologies with large specific surface area of 141.6 m 2/g. The sensing films were prepared by spin coating on Al 2O 3 substrate with interdigitated Au electrode. The sensing films were tested toward some important toxic (NO 2, CO, SO 2) and flammable (H 2, C 2H 2) gases. It was found that SnO 2 sensing film showed excellent response and selectivity for NO 2 at a low operating temperature of 200 °C. In addition, the response linearly increased and the response time drastically decreased with increasing gas concentration. Therefore, the spin-coated flame-spray-prepared SnO 2 sensor is one of the most promising candidates for highly sensitive and selective detection of noxious NO 2 gas. © 2012 Elsevier B.V. All rights reserved.